Utility of COX-2 as Immunohistochemical Prognostic Marker in Relation to Various Histopathological Parameters and TNM Staging in Colorectal Carcinoma - Sreetama Mukherjee; Sunita Vagha; Samarth Shukla; Anup Kediya; Suvidha S Tammewar (Journal of Clinical and Diagnostic Research, 2023)
Introduction: The most prevalent neoplasm of the gastrointestinal system is colorectal carcinoma. After lung and breast carcinoma, malignant colorectal cancer appears to be characterised by inflammation. Among the numerous recognised indicators of inflammation, Cyclooxygenase-2 (COX-2) has been identified as playing a key role in the early phases of carcinogenesis. The link between higher expression of COX-2 and the early stages of carcinogenesis and cancer development implies that COX-2 might be a target for pre-cancerous colorectal lesion imaging. Aim: To assess the expression of COX-2 in colorectal carcinoma and the association with various histopathological parameters and Tumour Node Metastasis (TNM) staging. Materials and Methods: The current study is an observational, cross-sectional, retrospective, and prospective study that will take place in the Histopathology and Immunohistochemistry unit of the Department of Pathology, Jawaharlal Nehru Medical College, Sawangi (Meghe), Wardha, Maharashtra, India. Sample collection will be done during the the period of august 2021 to july 2024. The study included approximately 60-65 resected specimens from confirmed and planned Colectomy, Hemicolectomy, and Proctocolectomy specimens received in the Department of General Pathology, JNMC. Observations and results will be collected from the immunohistochemistry study by using COX-2 as a prognostic marker in colorectal carcinoma and correlating it with the TNM staging. Statistical analysis will be made by chi-square test and regression analysis.